Sequência didática e aprendizagem significativa das Leis de Newton - Oliveira, Marilene de Almeida (2021)
This dissertation presents a Didactic Sequence (DS) on Newton's Laws whose objective to study Inertia, the Fundamental Principle of Dynamics and Action and Reaction from the investigation, elaboration, experimentation and evaluation of the functioning of a medieval weapon called catapult. We were guided by the Theory of Meaningful Learning, proposed by David Ausubel, in order to relate theory and practice to the teaching of physics. In this perspective, we combine the teaching of Newtonian laws with the students' cognitive learning process, having as a theoretical-methodological reference the construction of a Didactic Sequence produced from a Potentially Significant Teaching Unit, consisting of a pre-test, lectures with significant content, workshop, concept maps and post-test guided by a previous organizer (catapult), for a 1st grade high school class from the school “Escola Estadual 13 de Maio”, located in the municipality of Tangará da Serra, Mato Grosso. We believe that the results of this study were positive for the significant learning of Newton's Laws by the students participating in the research, because they were able to understand the relationship between projectile launching and the three laws, in addition to serving as a pedagogical product for physics teachers, in order to enable an alternative to teach and learn Physics by attributing content meanings to their realities.